Clumped and oxygen isotope data of aragonite veins from ultramafic and mafic rocks recovered from the Wadi Tayin Massif, Samail Ophiolite, Oman Drilling Project Phase II - Lotta Ternieten; Gretchen L Früh-Green; Stefano M Bernasconi (PANGAEA, 2021)
The clumped and oxygen isotopes of aragonite from ultramafic, and mafic rocks recovered during ICDP Expedition 5057, Oman Drilling Project Phase II (November 2017 to February 2018) on the Wadi Tayin Massif, Samail Ophiolite, was examined to characterize carbon sources, speciation, and the fate of organic and inorganic carbon during natural large-scale hydration and carbonization. The measurements were performed at the ETH Zurich from 2017 to 2020 using a Kiel IV carbonate device interfaced with a ThermoFisher Scientific MAT253 isotope ratio mass spectrometer.
In: Ternieten, L et al. (2021): Carbon and oxygen geochemistry of the mantle peridotites of the Wadi Tayin Massif, Samail Ophiolite, ICDP Expedition 5057 Oman Drilling Project [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937673